The Use of Pair Check Strategy in Teaching Reading Comprehension on Narrative Text to Junior High School Students - Patria Ningsih; Rusdi Noor Rosa (Universitas Negeri Padang, 2019)
AbstractThis paper discusses how to use Pairs Check Strategy in teaching reading comprehension on narrative text at Junior High School. Based on the writers’ experience in teaching English, many students find the difficulties in reading, especially reading narrative text. The teacher can use Pair Check Strategy to teach reading comprehension in teaching and learning process. This strategy is applied to help students solve problems in reading. This strategy allows the students to share ideas, opinion, and check their comprehension each other with their discussion pairs. By applying the Pairs Check Strategy in reading narrative text, the teacher can reach the goal of teaching narrative text to junior high school students. In other words, this strategy can help teacher in teaching reading narrative text to the students.Keywords: Teaching reading, reading comprehension, narrative text, pairs check strategy.